A methodology and a tool to design of mixed-signal technology - Da Silva, Alexandre César Rodrigues [UNESP]; Grout, Ian (My University, 2007)
This paper presents a tool box developed to read files describing a SIMULINK® model and translates it into a structural VHDL-AMS description. In translation process, all files and directory structures to simulate the translated model on SystemVision™ environment is generate. The tool box named MS2SV was tested by three models of commercially available digital-to-analogue converters. All models use the R2R ladder network to conversion, but the functionality of these three components is different. The methodology of conversion of the model is presents together with sort theory about R-2R ladder network. In the evaluation of the translated models, we used a sine waveform input signal and the waveform generated by D/A conversion process was compared by FFT analysis. The results show the viability of this type of approach. This work considers some of challenges set by the electronic industry for the further development of simulation methodologies and tools in the field of mixed-signal technology. © 2007 IEEE.
Keywords: Automation; Automobile electronic equipment; Automobile parts and equipment; Computer hardware description languages; Speed; Automotive Mechanics; Mixed-signal technology; Translation processes; VHDL AMS; Model structures